Electrochemical attributes and availability of nutrients/toxic elements, and heavy metals in soil of chowki, Rajandgaon Chhattisgarh - Bhui, Ashish Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Electrochemical properties of soils are very important for the understanding of the physico-chemical phenomena which affect soil toxicity, fertility and the availability of nutrients for plants and ground water which indirectly infiltrates in the ecological cycle. This paper highlights the electrochemical properties of tropical soils in Rajnandgaon, the behavior and the availability of Some toxic elements, nutrients and heavy metals especially for soils with predominant variable charge minerals in Ambagarh Chowki Chhattisgarh where already heavy toxicity of Arsenic in drinking water had been reported. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->